Bovine Antibody-Based Oral Immunotherapy for Reduction of Intragastric Helicobacter pylori Colonization: A Randomized Clinical Trial. (2011) - den Hoed, CM; de Vries, AC; Mensink, PBF; Dierikx, CM; Suzuki, H; Capelle, L; van Dekken, H; Ouwendijk, R; Kuipers, EJ
Abstract : BACKGROUND: Antibiotic-based regimens are frequently used for the treatment of Helicobacter pylori infection. These regimens fail to eradicate H pylori in 15% to 40% of patients, primarily due to antimicrobial resistance and insufficient patient compliance. Effective prevention and eradication of H pylori by passive immunization with orally administered bovine antibodies has been demonstrated in animal studies, and may serve as an alternative therapy in humans. OBJECTIVE: To study the efficacy and safety of orally administered bovine anti- H pylori antibodies for the reduction of intragastric bacterial load and eradication of H pylori in humans. METHODS: Dairy cows were immunized against H pylori. After confirmation of the presence of anti- H pylori antibodies in the milk, the milk was subsequently processed into a whey protein concentrate (WPC). In a prospective, double-blind, placebo-controlled randomized clinical trial, H pylori -infected subjects were randomly assigned to treatment with the WPC preparation or placebo. Study medication was continued for 28 days; subjects were followed-up for 56 days. RESULTS: Of the 30 subjects included, 27 completed the protocol. Of these 27 evaluable subjects, 14 were treated with WPC and 13 with placebo. There was no significant difference in urea breath test decrease between the WPC- and placebo-treated group (P=0.75). H pylori -associated gastritis and density were not significantly reduced in either group after treatment (P>0.05 for all). CONCLUSION: Bovine antibody-based oral immunotherapy appears to be safe, but does not significantly reduce intragastric H pylori density in humans. Further studies are needed to determine whether WPC treatment has additional value to conventional antibiotic treatment for H pylori .